Entrepreneurial ecosystems in smart cities for tourism development: From stakeholder perceptions to regional tourism policy implications. (December 2020) - Eichelberger, Sarah; Peters, Mike; Pikkemaat, Birgit; Chan, Chung-Shing
Abstract: Studies from the field of smart city development show that smart cities attract more people from the nearby countryside along with an increasing number of tourists. While many smart tourism concepts focus solely on the development of technology, people, and institutional logic, the entrepreneurial ecosystem (EES) approach helps to strengthen smart destinations on their way to fostering the development of urban sustainability. As part of an evaluation of the EES, qualitative interviews (n = 14) with key informants demonstrate the importance of entrepreneurship for the development of smart destinations. To identify the relevant factors for this kind of smart city positioning, the following study aims to explore, test, and analyze smart city aspects among experts in terms of EES, residents, and tourists visiting Innsbruck. The present study uses both face-to-face interviews and surveys to explore initiatives and targets within the city's EES development as perceived by core stakeholders. It applies a questionnaire measuring local residents' and tourists' perceptions of important smart city attributes (n = 336). The data shows that residents believe Innsbruck has the potential to become a smart city. Furthermore, the data confirms that the EES approach benefits from the tourism industry in the region, with tourism found to improve the respective EES elements, consequently leading to enhanced entrepreneurial activity.